(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2025)
This study presents a geophysical investigation of subsurface structures within the metaigneous terrains of selected area located in Jeli, Kelantan using integrated Electrical Resistivity Imaging (ERI) and Induced Polarization (IP) methods. The study area is located within Universiti Malaysia Kelantan Jeli Campus, Jeli District, Kelantan, and lies within the Central Belt of Peninsular Malaysia. Geological mapping at this area revealed the presence of metaigneous rocks, offering critical insights into the lithological distribution and structural deformation history of the region. Geophysical surveys along selected profiles delineated variations in resistivity and chargeability, identifying key features such as fractured zones, weathered layers, and compact bedrock. High resistivity and moderate-to-high chargeability values correspond to intact metaigneous rock bodies, while lower values indicate weathered or altered zones. The integration of ERI and IP data with surface geological observations provides a comprehensive model of the subsurface, offering insights valuable for Rare Earth Element (REE) mineral exploration.